Civil liability of doctors and the employment relationship - Stępniak, Piotr (Journal of Medical Science, 2016)
Article takes the issue of liability of doctors in connection with the provision of health services. The author suggests that this responsibility depends on the type of their employment by the therapeutic entity. So it is regulated by civil law and labor law. Therapeutic entity is as responsible as a company, ie. on the basis of risk. Responsibility of the doctor depends on whether he is employed on the basis of a civil contract, or contract of employment. The author widely discusses implications of different employment contracts. He indicates that the best situation the doctor has as an employee within the meaning of the Labor Code. His liability is in this case reduced to a minimum, i.e. up to 3 – monthly salaries. In the case of civil law contracts, the liability is unlimited. Therefore, the author recommends in the conclusions, that doctors should make contracts of liability insurance.